Macroprolactinemia Detection by Magnetically Assisted Polyethylene Glycol Precipitation: Potential for Automation. (24th March 2020) - Smith, Thomas; Stern, Eric; Tan, Enqing; Vacic, Aleksandar; Fahie-Wilson, Michael
Abstract: Background: Macroprolactin is an immunoglobulin-prolactin complex that is not bioactive in vivo but the prolactin component remains immunoreactive. The complex is a universal source of interference in prolactin immunoassays and commonly results in misdiagnosis of hyperprolactinemia with consequent clinical mismanagement of patients. Removal of macroprolactin by precipitation with polyethylene glycol (PEG) is an effective technique for identifying such patients but unfortunately not universally employed due to the manual nature of the procedure. Methods: We developed a modified PEG precipitation technique using magnetic nanoparticles that we termed Magnetically Assisted PEG Precipitation (MAPP). This procedure was verified against an established PEG precipitation procedure. Results: The MAPP procedure we developed was robust, reproducible, and affords the potential for automation of macroprolactin screening in clinical laboratories. Comparisons of prolactin levels obtained following MAPP in sera from patients with either true hyperprolactinemia or macroprolactinemia generated results comparable to that of conventional PEG precipitation. Conclusions: The MAPP technique yields results comparable to those of traditional PEG precipitation. Elimination of the need for centrifugation affords the possibility of automation and hence more widespread adoption of routine PEG screening by clinical laboratories.